Faktor-faktor yang mempengaruhi rasio pembayaran dividen perusahaan pertanian dan pertambangan - Rosinta Ria Panggabean; Antonius Martin (Jurnal Akuntansi, 2020)
The main purpose of this research was to determine the effect of Cash Ratio (CR), Sales Growth (SG), and Investment Opportunity Set (IOS), on Dividend Payout Ratio (DPR). This quantitative research used a sample of 18 agriculture and mining companies listed in Indonesia Stock Exchange (IDX) within the period of 2013-2017. The data used in this research were ssecondary data such as financial statement and annual reports. Data analysis employed panel data regression test with Eviews program version 10. The results of hypothesis testing show that cash ratio has a significant and positive effect on dividend payout ratio, but sales growth and investment opportunity set do not have a significant effect on dividend payout ratio. Meanwhile, the simultaneous hypothesis results show that cash ratio, sales growth, and investment opportunity set have an effect on dividend payout ratio. This study adds new independent variables that are different from the reference research, namely the cash ratio and investment opportunity set.